Worth fighting for : love, loss and moving forward - Swayze, Lisa Niemi (New York : Atria Books, 2012)
This memoir from the author of The Time of My Life (written with her husband Patrick Swayze) a remarkable, new account of grief, loss, caregiving, and moving on, with never before revealed stories of the Swayzes' final months together. Lisa Niemi and Patrick Swayze first met as teenagers at his mother's dance studio. He was older and just a bit cocky; she was the gorgeous waif who refused to worship the ground he walked on. It didn't take long for them to fall in love. Their thirty-four year marriage, which they explored together in The Time of My Life, was a uniquely passionate partnership.
Fairytale -- The diagnosis -- It ain't over til it's over -- Uncharted territory -- Everybody finds out -- The troops arrive -- In God we trust, all others bring data -- Russian roulette -- Embracing the alligator -- The beast - - If you call me captain, I'll call you daddy -- Dancing as fast as we can -- Dark nights, graced with snow -- Gimme something real -- Abraxane: the breast cancer drug - - Just your daily 911 emergency -- Outrunning the ambulance chasers -- Rallies again -- And another thing -- My secret weapon -- The last infection -- One more decision -- Home at last -- The immediate aftermath.
Keywords: Swayze, Patrick -- Health; Niemi, Lisa; Pancreas -- Cancer -- Patients -- United States -- Biography; Caregivers -- United States -- Biography; Motion picture actors and actresses -- United States -- Biography